2005
DOI: 10.2166/wh.2005.0016
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized, controlled trial of an in-home drinking water intervention among HIV+ persons

Abstract: Although immunocompromised persons may be at increased risk for gastrointestinal illnesses, no trials investigating drinking water treatment and gastrointestinal illness in such patients have been published. Earlier results from San Francisco suggested an association (OR 6.76) between tap water and cryptosporidiosis among HIV + persons. The authors conducted a randomized, triple-blinded intervention trial of home water treatment in San Francisco, California, from April 2000 to May 2001. Fifty HIV-positive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Most studies were undertaken in lower middle or low-income countries based on World Bank criteria, but three studies were conducted in the USA (Colford 2002 USA; Colford 2005 USA; Colford 2009 USA), one in Australia (Rodrigo 2011 AUS), and one in Saudi Arabia (Mahfouz 1995 KSA). Five studies were conducted in urban settings (Semenza 1998 UZB; Colford 2002 USA; Colford 2005 USA; Colford 2009 USA; Rodrigo 2011 AUS), five in peri-urban settings (Quick 1999 BOL; Quick 2002 ZMB; du Preez 2010 ZAF; Jain 2010 GHA; Peletz 2012 ZMB), two in urban informal or squatter settlements (Handzel 1998 BGD; Luby 2004), two in camps for refugees or displaced persons (Roberts 2001 MWI; Doocy 2006 LBR), five in multiple settings (URL 1995; Clasen 2005 COL; Stauber 2009 DOM; du Preez 2011 KEN; Boisson 2013 IND), and the others in villages or other rural settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were undertaken in lower middle or low-income countries based on World Bank criteria, but three studies were conducted in the USA (Colford 2002 USA; Colford 2005 USA; Colford 2009 USA), one in Australia (Rodrigo 2011 AUS), and one in Saudi Arabia (Mahfouz 1995 KSA). Five studies were conducted in urban settings (Semenza 1998 UZB; Colford 2002 USA; Colford 2005 USA; Colford 2009 USA; Rodrigo 2011 AUS), five in peri-urban settings (Quick 1999 BOL; Quick 2002 ZMB; du Preez 2010 ZAF; Jain 2010 GHA; Peletz 2012 ZMB), two in urban informal or squatter settlements (Handzel 1998 BGD; Luby 2004), two in camps for refugees or displaced persons (Roberts 2001 MWI; Doocy 2006 LBR), five in multiple settings (URL 1995; Clasen 2005 COL; Stauber 2009 DOM; du Preez 2011 KEN; Boisson 2013 IND), and the others in villages or other rural settings.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six studies used the WHO's definition of diarrhoea, while other studies used the following definitions: the mother's or respondent's definition (Austin 1993; Gasana 2002 RWA; Reller 2003; Crump 2005; Chiller 2006 GTM); 'watery diarrhoea as a component of gastroenteritis' (Colford 2002 USA; Colford 2005 USA; Colford 2009 USA; Rodrigo 2011 AUS); the local term (Conroy 1996 KEN; Conroy 1999 KEN; Boisson 2009 ETH); "significant change in bowel habits towards decreased consistency or increased frequency" (Kirchhoff 1985 BRA); or dysentery (du Preez 2010 ZAF; du Preez 2011 KEN). Four studies did not report the case definition used for diarrhoea (Torun 1982 GTM; Xiao 1997 CHN; GĂŒnther 2013 BEN; Lindquist 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third inclusion criterion was the use of epidemiological methods to link exposures to health outcomes; studies using a risk assessment approach to infer GII outcomes from water quality data were excluded because they use theoretical transmission models that rely on several assumptions (Soller 2006) to estimate disease risk, in contrast to epidemiological methods that measure disease outcomes directly. Finally, because the objective of our review was to characterize the risk of endemic GII among general populations that are exposed to distribution system deficiencies, we excluded studies on specific subpopulations that are particularly vulnerable to GII from waterborne pathogens, such as the elderly and immunocompromised (Colford et al 2005a, 2009; Gerba et al 1996) or individuals that are not representative of a resident population, such as travelers (Ericsson 1998). The review was limited to studies in English, German, or Spanish (the languages spoken by the authors), with no limitations on study location or quality.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to keep in mind that these cryptosporidiosis risk factors are relevant in industrialized nations and that the settings and challenges are very different in developing countries. In immunocompromised subjects, mainly those with HIV infection, several studies investigated the specific risk factors for this high-risk group and found that the drinking of tap water from an untreated supply, exposure to pets and animals, unsafe sexual activity, and the use of public toilets are associated with Cryptosporidium infection (91)(92)(93).…”
Section: Cryptosporidiosismentioning
confidence: 99%